Physiological responses to an intensified period of Rugby League competition - Johnston, R. D.; Gibson, N. V.; Twist, C.; Gabbett, T. J.; MacNay, S. A.; MacFarlane, N. G. (The Journal of Strength and Conditioning Research, 2013)
This study investigated the physiological responses to an intensified period of rugby league competition and the subsequent impact on match performance. The participants were 7 rugby league players competing in an international student tournament. The tournament involved three 80-minute games over a 5-day period, with 48 hours between each match. Baseline measures of upper and lower body neuromuscular functions via a plyometric press-up (PP) and countermovement jump (CMJ), respectively (peak power and peak force were measured), blood creatine kinase (CK), and perceptions of well-being were assessed with a questionnaire. These measures were repeated every morning of the competition; neuromuscular fatigue and CK were additionally assessed within 2 hours after the cessation of each game. During each match, player movements were recorded via global positioning system units. There were meaningful reductions in upper (effect size [ES] = -0.55) and lower body (ES = -0.73) neuromuscular functions, and perceptual well-being (ES = -1.56) and increases in blood CK (ES = 2.32) after game 1. These changes increased in magnitude as the competition progressed. There were large reductions in the relative distance covered in high-speed running (ES = -1.49) and maximal accelerations (ES = -0.85) during game 3. Additionally, moderate reductions in the percentage of successful tackles completed were observed during game 3 (ES = -0.59). Collectively, these results demonstrate that during an intensified period of rugby league competition, characterized by only 48 hours between matches, fatigue will accumulate. This cumulative fatigue may compromise high-intensity match activities such as high-speed running, accelerations, and tackling. Furthermore, CMJs and PPs appear to be sensitive measures for monitoring neuromuscular function in rugby league players.